Implementasi Media Pembelajaran Audio Visual Pada Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti Di Kelas VII SMP Widya Sakti Denpasar - Utama, I Putu Shandy Palguna (Jayapangus Press, 2021)
Audio visual learning media is a medium that acts as an intermediary in the learning process in the form of sight and hearing which can activate the atmosphere of students so that they are able to gain knowledge, skills or shape students' attitudes in helping to achieve learning goals. The purpose of the study was to analyze the implementation of audio-visual learning media in learning Hindu religious education and Budi Pekerti in class VII SMP Widya Sakti Denpasar. The data collection methods used are interviews, observations, literature studies, document studies. The research results show: (1) In developing audio visual media, syllabus analysis and analysis of facility and infrastructure needs are needed. (2) The application of audio visual media is found in the learning process in the classroom with the teacher and students in the classroom. In the process of using audio-visual media, there are obstacles experienced by teachers and students. To overcome these obstacles, teachers and students have made efforts to optimize the learning process using audio-visual media. (3) In implementing audio visual media there are implications for teachers and students.